Search for the standard model higgs boson in the H→WW→lνq ′q̄ decay channel - Abazov, V. M. (2011)
We present a search for the standard model Higgs boson (H) in pp̄ collisions at √s=1.96TeV in events containing a charged lepton (ℓ), missing transverse energy, and at least two jets, using 5.4fb-1 of integrated luminosity recorded with the D0 detector at the Fermilab Tevatron Collider. This analysis is sensitive primarily to Higgs bosons produced through the fusion of two gluons or two electroweak bosons, with subsequent decay H→WW→ℓνq′q̄, where ℓ is an electron or muon. The search is also sensitive to contributions from other production channels, such as WH→ℓνbb̄. In the absence of a signal, we set limits at the 95% C.L. on the cross section for H production σ(pp̄→H+X) in these final states. For a mass of M H=160GeV, the limit is a factor of 3.9 larger than the cross section in the standard model and consistent with an a priori expected sensitivity of 5.0. © 2011 American Physical Society.